LGPD e Administração Pública: regulação e aplicação - Lima, José Jerônimo Nogueira de (2021)
The objective of the work entitled “LGPD and Public Administration: regulation and application” is to highlight aspects related to the General Law for the Protection of Personal Data, especially those inherent to the regulatory body and the situations in which the law is applied, or not, to Public Administration, through research on doctrine, jurisprudence, academic works and journalistic articles. The conclusions reveal a need to give greater independence to the National Data and Protection Authority, as a regulator, as well as compliance with constitutional principles and the general data protection law to the Administration, both in the cases in which the law applies to the Government, as well as in the cases in which it does not apply